Efficient fabrication method for nitrogen-vacancy color centers for a biomarker - Suk, Jaekwon; Lee, Jaeyong; Kim, Joonkon; Song, Jonghan (KOREAN PHYSICAL SOC, 2015)
Nitrogen-vacancy (NV) color centers in nanodiamond (ND) are fabricated through three steps, high-energy ion irradiation on ND, high-temperature (800 a"integral) annealing in vacuum and lowtemperature (500 a"integral) annealing in air. Raman measurements show that a surface-graphite layer is formed after annealing at 800 a"integral in vacuum while the graphite formed during ion irradiation is below the detection limit. Annealing at 500 a"integral in air is a crucial step in removing the graphite layer from ND that is ion-irradiated and 800 a"integral-annealed. A strong luminescence from NV color center is observed only after annealing at 500 a"integral in air.
Keywords: FLUORESCENT NANODIAMONDS; DIAMOND